ТАДБИРКОР АЁЛ ШАХСИНИНГ ИНДИВИДУАЛ ВА ИЖТИМОИЙ-ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Елмуратова, А.У. (SCIENCE and SOCIETY, 2017)
In the article the issues of individual-psychological features of woman personality were investigated. It contains the information about mental potential and intellectual features of women who are engaged in small business. There are some opinions about necessity of communicative quality in businesswomen, the necessity to be skillful in ethical treatment with people in everyday life. Dealing with small business it is necessary to take into account the factors of effective fulfillment of labour duties. It is emplasized that businesswomen should meet the reguirements of market economy.
Keywords: personality; small business; labour activity; freedom; endowmets; dialogue; motivation to achieve victory; self assurance; character; feeling; spiritual- physiological quality